World Workshop on Oral Medicine VI: a systematic review of medication‐induced salivary gland dysfunction. (20th January 2016) - Villa, A; Wolff, A; Narayana, N; Dawes, C; Aframian, DJ; Lynge Pedersen, AM; Vissink, A; Aliko, A; Sia, YW; Joshi, RK; McGowan, R; Jensen, SB; et al.
Abstract : The aim of this paper was to perform a systematic review of the pathogenesis of medication‐induced salivary gland dysfunction (MISGD). Review of the identified papers was based on the standards regarding the methodology for systematic reviews set forth by the World Workshop on Oral Medicine IV and the PRISMA statement. Eligible papers were assessed for both the degree and strength of relevance to the pathogenesis of MISGD as well as on the appropriateness of the study design and sample size. A total of 99 papers were retained for the final analysis. MISGD in human studies was generally reported as xerostomia (the sensation of oral dryness) without measurements of salivary secretion rate. Medications may act on the central nervous system (CNS) and/or at the neuroglandular junction on muscarinic, α ‐and β ‐adrenergic receptors and certain peptidergic receptors. The types of medications that were most commonly implicated for inducing salivary gland dysfunction were those acting on the nervous, cardiovascular, genitourinary, musculoskeletal, respiratory, and alimentary systems. Although many medications may affect the salivary flow rate and composition, most of the studies considered only xerostomia. Thus, further human studies are necessary to improve our understanding of the association between MISGD and the underlying pathophysiology.